Features of Modeling the Operating Modes of Outdoor Lighting Lines - V. N. Kalechyts (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The necessity of modeling the operating modes of outdoor lighting lines with a voltage of 0.23/0.4 kV is substantiated. The choice of the optimal configuration of the lighting line while ensuring the standardized values of illumination and brightness on the working surface is recommended to be carried out by comparing several variants with different positions of pillars, types of light intensity curves, the number and power of luminaires. The results of the lighting calculation are the basis for modeling the electrical operation modes of outdoor lighting lines, which allows determining the operating parameters (node voltage, active and reactive power, current, voltage drop, loss of active and reactive power in individual sections). The obtained data can be used to select the cross-sectional area of conductor cores and forecast the power consumption of outdoor lighting, taking into account the specific features of light flux regulation (dimming). As a rule, outdoor lighting lines are connected to one power point. The use of outdoor lighting lines with bilateral supply for main streets and circular roads of relatively long length is proposed which will not only make it possible to increase the reliability of power supply of lighting installations, but also to use conductors with a smaller cross-section area of the cores. The electrical load of light sources is assumed on the basis of static characteristics. Modeling of the electrical modes of the outdoor lighting network is carried out taking into account the higher harmonics of current and voltage. The rational operation mode of the outdoor lighting line is determined by the magnitude of the voltage deviation from the nominal value, the indicators of non-sinusoidality and voltage asymmetry at the power supply point. Additional possibilities for modeling the modes of operation of lighting lines are to search for damage (detection of short circuits, determination of the presence of faulty lamps).